2018
DOI: 10.1371/journal.pone.0206930
|View full text |Cite
|
Sign up to set email alerts
|

The long term effect of metabolic profile and microbiota status in early gastric cancer patients after subtotal gastrectomy

Abstract: Long term effects of subtotal gastrectomy on gut microbiota modifications with subsequent metabolic profiles are limited. We aimed to investigate and compare long-term effects of metabolic profiles and microbiota status in early gastric cancer patients post curative subtotal gastrectomy to the controls. In this cross-sectional study, we analyzed type II diabetes mellitus and metabolic syndrome occurrence in two groups: 111 patients after curative subtotal gastrectomy with Billroth II (BII) anastomosis and Roux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 42 publications
(53 reference statements)
3
31
1
2
Order By: Relevance
“…Higher Shannon diversity indices were conserved across the three major phyla: Firmicutes (mOTU: p=8.98×10 −7 ; MetaPhlAn2: p=2.91×10 −4 ), Actinobacteria (mOTU: p=7.69×10 −4 ; MetaPhlAn2: p=0.0419) and Bacteroidetes (mOTU: p=0.225; MetaPhlAn2: p=0.0283) (figure 2E and F). Our results were in accordance with previous studies, in that species diversity was higher in patients with postgastrectomy gastric cancer12 and obesity9 32 33 than in non-surgical participants.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Higher Shannon diversity indices were conserved across the three major phyla: Firmicutes (mOTU: p=8.98×10 −7 ; MetaPhlAn2: p=2.91×10 −4 ), Actinobacteria (mOTU: p=7.69×10 −4 ; MetaPhlAn2: p=0.0419) and Bacteroidetes (mOTU: p=0.225; MetaPhlAn2: p=0.0283) (figure 2E and F). Our results were in accordance with previous studies, in that species diversity was higher in patients with postgastrectomy gastric cancer12 and obesity9 32 33 than in non-surgical participants.…”
Section: Resultssupporting
confidence: 93%
“…Tseng et al revealed that subtotal gastrectomy altered the diversity, community composition and predicted gene functions of gastric microbiota, which associated closely with the altered gastric environment after surgery 11. Lin et al confirmed these findings by analysing the faecal microbiome over the long term after gastrectomy 12. They showed that patients with subtotal gastrectomy, and in particular Roux-en-Y gastrojejuno anastomosis, had subsequent lower occurrence of type II diabetes and metabolic syndrome than the controls.…”
Section: Introductionmentioning
confidence: 97%
“…Bacterial genomic microbial DNAs was extracted for direct use in 16S rRNA gene sequencing. [17,18] The amounts and quality of isolated genomic DNA was determined with NanoDrop ND-1000 (Thermo Scienti c, Wilmington, DE, USA). Genomic DNA was stored at -80 °C prior to 16S rRNA sequencing.…”
Section: Stool Bacterial Genomic Dna Extraction and Pcr Ampli Cationmentioning
confidence: 99%
“…Dual-indexes (barcodes) was used for each sample before sequencing and next-generation sequencing was performed by the Illumina MiSeq Desktop Sequencer following the standard protocol. [18] Data processing and statistical analysis The raw sequencing reads were assembled using FLASH v.1.2.7. [19] The quality of reads was assessed by QIIME 1.9.1 pipeline and low-quality reads (Q <20) were truncated.…”
Section: Stool Bacterial Genomic Dna Extraction and Pcr Ampli Cationmentioning
confidence: 99%
“…Пациенты со злокачественным образованием желудка, перенесшие субтотальную резекцию желудка по Бильрот II и в модификации по Ру, в послеоперационном периоде имели сни-жение ИМТ, уменьшение окружности талии, повышение уровня ЛПВП в сыворотке крови, снижение уровня ТГ и уровня глюкозы в сыворотке крови по сравнению с контрольной группой. У этих пациентов значительно ниже частота возникновения сахарного диабета II типа и метаболического синдрома, а также увеличение микробиота кишечника после субтотальной резекции в модификации по Ру [11]. Однако при наличии метаболического синдрома увеличение микробиоты при отсутствии адекватной перистальтической волны приводит к развитию локальной инфекции в зоне анастомоза, запуская вышеописанный каскадный механизм иммунного ответа.…”
unclassified